2016
DOI: 10.1007/s10562-016-1797-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Immobilized Lipase on Fe3O4 Nanoparticles as Nano biocatalyst for the Synthesis of Benzothiazepine and Spirobenzothiazine Chroman Derivatives

Abstract: A retrievable nanostructure heterogeneous catalyst, based on lipase (lipase from the fungus Aspergillus niger), namely Fe 3 O 4 -bonded lipase (Fe 3 O 4 NPs@ lipase) was prepared in nano size and fully characterized by several techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, Scanning electron microscopy, Transmission electron microscopy and Vibrating sample magnetometer. The retrievable nanostructure catalyst was asserted to be an efficient catalyst in the synthesis of benzothiaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…The comparison of free and immobilized lipase revealed that immobilizing A. terreus Lipase on CeO 2 @PDA increased the flexibility of lipase to a wide pH range, compared to free lipase. Our results were comparable to the studies of Baharfar and Mahajer [13].…”
Section: Effect Of Ph and Temperature On Activity Of Nano-biocatalystsupporting
confidence: 91%
See 1 more Smart Citation
“…The comparison of free and immobilized lipase revealed that immobilizing A. terreus Lipase on CeO 2 @PDA increased the flexibility of lipase to a wide pH range, compared to free lipase. Our results were comparable to the studies of Baharfar and Mahajer [13].…”
Section: Effect Of Ph and Temperature On Activity Of Nano-biocatalystsupporting
confidence: 91%
“…It was found that, by using polydopamine, high immobilization efficiency was achieved by using CeO2 nanorods because polydopamine and CeO2 nanorods formed the complex, which was found to be efficient regarding immobilization of lipase. The wider surface was available during the reaction, which gave higher conversion rate in a short period of time by using the lipase-immobilized nanorods for biodiesel production [13]. To the best of our knowledge, the synthesized nano-…”
Section: Lipase Activity Assaymentioning
confidence: 99%
“…Considering the above reports and in continuation of our previous studies in the development of the simple and effective multicomponent reactions for the synthesis of novel heterocyclic compounds by heterogeneous catalysts, we wish to report a facile route to fabrication of Fe 3 O 4 /GO/Au‐Ag nanocomposite, which exhibits superior catalytic activity for the efficient preparation of Spiro[indoline‐3,5′‐pyrido[2,3‐ d :6,5‐ d ’]dipyrimidine]‐pentaone derivatives from a wide diversity of isatin, 6‐aminouracil and different 1,3‐dicarbonyl compounds in water under green and mild reaction conditions. Many of methods reported for the synthesis of spirooxindole compounds suffer from disadvantages such as high temperature, use of homogeneous catalyst, long reaction times, and the use of harmful organic solvent .…”
Section: Introductionmentioning
confidence: 99%
“…A plausible mechanism is illustrated in Scheme 3, which is supported by the previous literature. [8,40] To evaluate the recoverability and reusability of MgO@PMO-IL, we used this catalyst in the three- isatin under the optimized conditions. The catalyst was recovered through a simple filtration process and reused for at least seven times without a significant decrease in its catalytic activity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Due to expanding the scope of the IFB reaction, and in continuation of our previous works for the synthesis of novel heterocyclic compounds using heterogeneous catalysts, we have developed a strategy for the preparation of a novel MgO containing PMO‐IL (MgO@PMO‐IL) and examined its application in the Feist–Benary reaction for the synthesis of novel spirooxindole‐furan derivatives via three‐component reaction of isatin derivatives with 1,3‐dicarbonyl compounds and N ‐phenacyl pyridinium salts (Scheme ). The products were synthesized under green reaction conditions with excellent yields, low reaction time and simple work‐up in the presence of a highly efficient and recoverable nanocatalyst …”
Section: Introductionmentioning
confidence: 99%